Early Detection of Psychiatric Disorders and Counseling Service Rules: A Cross Sectional Study on University Students - Hastuti, Weni; Ratnasari, Nita Yunianti; Hidayah, Nur; Suyanti, Suyanti (Psikopedagogia, 2024)
Mental health become a crucial aspect in an individual's life, especially among students who are experiencing a dynamic developmental phase. The prevalence of mental health in Indonesia had reached 18,5%. It means that out of 1.000 residents are at least 185 people experiencing mental health disorders or in every household, and there is a family member suffering from mental health disorders. Several studies have shown that university students tend to experience high levels of stress and psychological distress that can negatively impact their mental well-being. Based on the above description, this study aims to determine and analyze the mental health status of university students using the SRQ 29 questionnaire. This type of research is quantitative research. The design used descriptive analytic with a cross sectional approach. This is a type of research in which the measurement of variables is carried out only once at a time. The study population involved all students on the campus of Institut Teknologi Sains dan Kesehatan (ITS) PKU Muhammadiyah Surakarta, and the sampling technique used a total sample where all those registered as FIK students in the 2023/2024 academic year and were required to be respondents in this study. The research instrument was used to measure mental emotional disorder variables and determine mental health status uses the Self-Report Questionnaire-29 (SRQ-29) from WHO. The questionnaire was given to students using Google form media. Inform consent was carried out before data collection, by explaining the purpose of the research. There is correlation between age and gender with the incidence of neurological symptoms and psychotic disorders.